Space Transition Theory in Cyber-Sexual Harassment of Female Content Creators on the TikTok Platform - Sherly Waruwu; Triny Srihadiati (Journal of Feminism and Gender Studies, 2025)
Cyber-sexual harassment is a form of online gender-based violence (GBV). Currently, it is increasingly prevalent on social media platforms, one of which is TikTok. The emergence of comments that contain sexual elements, objectification of the body. Many words whose meaning is shifted towards a negative direction whose purpose is to harass. This phenomenon indicates a shift in deviant behavior from real space to cyberspace, which demands a new theoretical approach in understanding the motivation of the perpetrator. This study aims to analyze the behavior of cyber sexual harassment perpetrators against female content creators on TikTok using Space Transition Theory (Karuppannan Jaishankar, 2008). This research uses a qualitative method with several data collection techniques, one of which is conducting in-depth interviews with perpetrators who admit to having made sexualized comments to female creators on TikTok. The data were analyzed by matching the field findings against the seven postulates in Space Transition Theory. The results show that the postulates in the theory appear in the behavior of the perpetrator, ranging from the release of behavior that is held back in the real world, the use of anonymity to avoid consequences, to the influence of virtual social norms that tend to tolerate acts of harassment. This phenomenon also shows the dynamic interaction between the real and virtual worlds, both in terms of behavior and social values. Space Transition Theory is relevant to explain the tendency of perpetrators to commit sexual harassment on social media, especially on platforms such as TikTok. This theory is an important foundation in understanding gender-based cybercrime from the perspective of perpetrator behavior.